Development of high refractive and high water content polythiourethane/AA hydrogels for potential artificial cornea implants. Issue 9 (12th June 2020) - Zeng, Youlan; Fan, Lu; Deng, Min; Sun, Peng; Zhang, Boxiao; Zhang, Quanyuan; Li, Ling; Xu, Zushun
Abstract: Two novel thiol-terminated monomers, ethylene glycol bis(mercaptoacetate) (EGBMA) and glycerol tri(mercaptoacetate) (GTMA), were prepared via esterification reaction of mercaptoacetic acid with ethylene glycol or glycerol. Then the synthesized thiol-terminated monomers were reacted with excess diisocyanates such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), 2, 4-toluene diisocyanate (TDI) or methylenediphenyl diisocyanate (MDI), followed by reacting with 2-hydroxyethyl methacrylate (HEMA) to get several different polymerizable polythiourethane (PTU) precursors. Subsequently, a series of high refractive index (RI) and high water content polythiourethane/acrylic acid (PTU/AA) hydrogels was successfully synthesized from the polythiourethane precursors via a simple ultraviolet-light-initiated free radical co-polymerization method. The resulting hydrogels are clear and transparent, and their RIs were measured to be as high as 1.514–1.548 and 1.396–1.441 in dry and hydrated state, respectively, and water content of the hydrogels can be reached 62.9–86.2%, which can be tuned by varying the structure of diisocyanate and polythiourethane, or the weight ratio of PTU to PAA. In vitro cytotoxicity assays suggested all the hydrogels exhibited low cytotoxicity towards human corneal epithelial cells (HCECs). Hence, the high RI and high water content hydrogels developed in this work might potentially be an excellent candidate for artificial corneal implants. Graphical Abstract: